(untitled) (Journal of Economic Research & Business Administration, 2016)
Authors consider process forecasting activity of economic agents on the basis of financial and economic indicators taking into account influence of the economic environment elements such as inflation, risks, participa tion in implementation of the various currencies project, interest rates, etc. The purpose of the analysis forecasting indicators of the economic agent effectiveness activity, taking into account risk factors and uncertain ty, consists in as much as possible to reduce the uncertainty connected with the income flows for various suppliers of the capital used by the com pany. In process to preparation of article for the purpose providing adapta tion of theorganizational aspects statement of finance management and development of financial policy for economic agents were been used for eign practice of finance management and the best practices of the Kazakh stan enterprises in this area.